EFEKTIVITAS EFFLEURAGE MASSAGE DENGAN AROMATERAPI LAVENDER TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA 1 FASE AKTIF DI BPM YENITA KOTA PARIAMAN - Miftakhul Zanah; Rika Armalini (Jurnal Ilmu Kebidanan, 2022)
ABSTRACT Background Labor pain that can not be overcome by the mother giving birth can cause problems and affect the condition of the mother in the form of fatigue, frustration, hopelessness and cause stress. The purpose of the study: to determine the effectiveness of effleurage massage with lavender aromatherapy on reducing the intensity of labor pain in the active phase of the 1st stage of labor at BPM Yenita Kota Pariaman Method: Quasy Experimental research design with one group pre test - post test design. This research was conducted from April to June 2021. The population in this study were all mothers who gave birth during the first active phase at BPM Yenita Pariaman City with a sample of 30 people, data analysis using the Wilxocon test. The results of the study: it was found that the average pain intensity in childbirth before the effleurage Massage and Lavender Aromatherapy was done was 6.00 and after the effleurage Massage and Lavender Aromatherapy was done was 4.60. The results showed that there was an effectiveness of giving effleurage Massage and Lavender Aromatherapy to reduce the intensity of labor pain in the active phase of the first stage of normal labor a (p value = 0.000). Conclusion: there is an effectiveness of giving effleurage Massage and Lavender Aromatherapy to reduce the intensity of labor pain in the active phase of the first stage of normal labor.